Do Iodine-Impregnated Adhesive Surgical Drapes Reduce Surgical Site Infections during Open Ventral Hernia Repair? A Comparative Analysis. Issue 6 (June 2017) - Moores, Neal; Rosenblatt, Steven; Prabhu, Ajita; Rosen, Michael
This study evaluated the role of iodine-impregnated adhesive drapes to reduce surgical site infections and occurrences in open ventral hernia repairs. All patients undergoing open ventral hernia repair of clean wounds with a retromuscular repair using synthetic mesh by a single surgeon were prospectively evaluated from the American Hernia Society Quality Collaborative. Patients were divided into those that had an Ioban drape and those that did not. The primary endpoints of this study were postoperative surgical site occurrence and infections. One hundred and four patients met inclusion criteria and were analyzed. There were 56 patients that received a 3M™ Ioban™ drape and 48 patients did not. The two groups were similar based on baseline demographics, risk factors, and operative details. There were four (7%) surgical site occurrences in the Ioban group (one wound cellulitis, one superficial surgical site infection, one allergic reaction to the Ioban, and one sterile seroma). There was one (2%) surgical site occurrence in the non-Ioban group (one superficial wound dehiscence). For patients undergoing clean ventral hernia repair with synthetic mesh placed in the retrorectus plane, the use of an iodine-impregnated drape does not result in a reduction in surgical site occurrences or superficial surgical site infections.